Case-control study of PD-1, PD-L1 and B7-H3 expression in lung cancer patients with and without human immunodeficiency virus (HIV) infection. (September 2018) - Scilla, Katherine A.; Zandberg, Dan P.; Bentzen, Søren M.; Mainor, Candace; Heath, Jonathon; Ioffe, Olga B.; Cellini, Ashley L.; Edelman, Martin J.; Riedel, David J.; Feliciano, Josephine L.
Highlights: HIV lung cancer patients had higher B7-H3 tumor expression than non-HIV controls. Expression of PD-L1 and PD-1 were similar in HIV lung cancer patients and controls. These data support inclusion of HIV lung cancer patients in immunotherapy trials. Abstract: Objective: Co-signaling molecules PD-L1, B7-H3, and PD-1 play a key role in cancer immunology. There are limited but emerging data on expression of these molecules in HIV-infected lung cancer patients. Materials and Methods: We reviewed archived lung cancer tissue samples from HIV-infected cases (n = 13) and HIV-uninfected controls (n = 13) from 2001-2015. Cases and controls were matched by histology and stage. Immunostained tumor sections were analyzed for percent of tumor cells expressing PD-L1 and B7-H3, and percent of tumor infiltrating immune cells (TII) expressing PD-1 and PD-L1. Positive expression was defined as >5%. Statistical analysis was performed using the non-parametric Mann-Whitney test and the chi-square test. Results: PD-L1 expression on tumor cells was positive in 23% of cases and 46% of controls. B7-H3 expression on tumor cells was positive in 92% of cases and 69% of controls. PD-1 expression on TII was positive in 69% of cases and 54% of controls. PD-L1 expression on TII was positive in 31% of cases and 69% of controls. B7-H3 percent expression on tumor cells was significantly higher in cases vs. controls (median 90% vs 20%, p = 0.005), but there were no significant differences in percent expression of PD-L1 on tumor cells, PD-1 on TII or PD-L1 on TII. Conclusion: HIV-infected lung cancer patients had significantly higher B7-H3 tumor expression compared to HIV-uninfected controls, with similar rates of tumor PD-L1 expression, as well as PD-1 and PD-L1 expression on TII. These results support inclusion of HIV-infected lung cancer patients in future immunotherapy trials.